1998
DOI: 10.1016/s0002-9270(98)00118-x
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's disease diagnosed by endoscopic ultrasound-guided fine needle aspiration of a periduodenal lymph node

Abstract: Hodgkin's disease rarely presents as obstructive jaundice. We report a case of Hodgkin's disease arising in periduodenallymph nodes, presenting with biliary obstruction, definitively diagnosed on cytologic material obtained by endosonographically-guided real-time fine needle aspiration biopsy and confirmed at laparotomy. The medical literature pertaining to the use of endosonography and fine needle aspiration biopsy for pancreatic lesions and abdominal lymphoma is reviewed. Currently available data support the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Hodgkin's disease rarely presents as obstructive jaundice and EUS-FNA can lead to definitive diagnosis, avoiding surgical intervention. 272…”
Section: Primary Biliary Tract Malignancymentioning
confidence: 99%
“…Hodgkin's disease rarely presents as obstructive jaundice and EUS-FNA can lead to definitive diagnosis, avoiding surgical intervention. 272…”
Section: Primary Biliary Tract Malignancymentioning
confidence: 99%
“…A number of studies have demonstrated that other diagnoses from mediastinal lesions can be obtained by EUS‐FNA. Most of these studies are a mixture of patients from retrospective studies 8,18 , 19,25 , 26,31 . The diagnoses obtained are TB, lymphoma, sarcoidosis, histoplasmosis, metastases from other primary tumors such as renal cancer, breast cancer, gynecologic cancer, esophageal cancer, gastric cancer and pancreatic cancer.…”
Section: Eus‐fna In Non‐lung Cancer Diseasementioning
confidence: 99%
“…EUS‐FNA can be used either to obtain a diagnosis from an unknown primary lesion in the mediastinum or to sample tissue from mediastinal lymph nodes in order to stage lung cancer or to differential diagnose other diseases involving lymph nodes of the mediastinum. EUS‐FNA is therefore relevant for evaluation of a variety of different mediastinal lesions 5–32 …”
Section: Introductionmentioning
confidence: 99%